2009
DOI: 10.1016/j.biopsych.2008.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline Decreases Alcohol Drinking and Seeking Behaviors Via Glial Cell Line-Derived Neurotrophic Factor

Abstract: Background-Cabergoline is an ergotamine derivative that increases the expression of glial cell line-derived neurotrophic factor (GDNF) in vitro. We recently showed that GDNF in the ventral tegmental area (VTA) reduces the motivation to consume alcohol. We therefore set out to determine whether cabergoline administration decreases alcohol-drinking and -seeking behaviors via GDNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 57 publications
2
61
1
2
Order By: Relevance
“…Systemic administration of cabergoline significantly reduces operant ethanol self-administration in rats [230]. Moreover, systemic administration of cabergoline reduced both the reacquisition of operant responding for ethanol after a period of extinction and cue-induces ethanolseeking after abstinence (which represents two different models of relapse) [230].…”
Section: Glial Cell Line-derived Neurotrophic Factor (Gdnf)mentioning
confidence: 98%
“…Systemic administration of cabergoline significantly reduces operant ethanol self-administration in rats [230]. Moreover, systemic administration of cabergoline reduced both the reacquisition of operant responding for ethanol after a period of extinction and cue-induces ethanolseeking after abstinence (which represents two different models of relapse) [230].…”
Section: Glial Cell Line-derived Neurotrophic Factor (Gdnf)mentioning
confidence: 98%
“…To trigger memory retrieval of operant responding for ethanol, the light cue (CS) and two primes of ethanol (0.1 ml of 10% ethanol, spaced by 1 min) were delivered at the beginning of the test session. Then, each press on the active lever resulted in the delivery of 0.1 ml of 10% ethanol during the entire self-administration session (30 min; Carnicella et al, 2009;Peana et al, 2009). …”
Section: Reacquisition Testingmentioning
confidence: 99%
“…This study showed that microinjection of either quinpirole or quinelorane, into the anterior part of the VTA dose-dependently decreased alcohol, but not sucrose, intake in alcoholpreferring rats [142]. In support are the data showing that local administration of cabergoline into the VTA reduced alcohol-seeking behaviour in rats [170]. These data are contradictory to the findings showing that the dopamine D2 receptor antagonist into the anterior VTA did not alter alcohol intake in high-alcohol-preferring rats [142].…”
Section: Preclinical Evidence For the Use Of Dopamine Agonists To Attmentioning
confidence: 61%
“…Moreover, cabergoline, a dopamine D2 receptor agonist, decreased alcohol intake, relapse drinking as well as alcohol-seeking behaviour in rodents [170]. In addition, low doses of bromocriptine produced a significant, dose-dependent shift in decreasing the preference for alcohol while enhancing water consumption [171], indicating that the compound at lower doses preferentially augment autoreceptor function, leading to decreased dopamine turnover with a blunted response to the rewarding effects of alcohol as a result.…”
Section: Preclinical Evidence For the Use Of Dopamine Agonists To Attmentioning
confidence: 97%